2017
DOI: 10.18632/oncotarget.18543
|View full text |Cite
|
Sign up to set email alerts
|

Novel tropolones induce the unfolded protein response pathway and apoptosis in multiple myeloma cells

Abstract: Tropolones are small organic compounds with metal-directing moieties. Tropolones inhibit the proliferation of cancer cell lines, possibly through their effects on metalloenzymes such as select histone deacetylases (HDACs). Pan-HDAC inhibitors are therapeutically beneficial in the treatment of multiple myeloma, however there is interest in the use of more selective HDAC inhibitor therapy to minimize adverse side effects. We hypothesized that tropolones might have anti-myeloma activities. To this end, a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…Pharmacokinetic assessment showed a half-life time of 93 min in mouse liver microsomes, as well as potential for glucuronidation, but no general cytotoxicity against human dermal fibroblast cells [ 170 ]. Further studies by Haney et al [ 171 ] identified 97 , which showed antiproliferative activities in the range of 1–11 µM against three different myeloma cell lines and exhibited a different apoptosis mechanism as a function of gene expression patterns compared to SAHA. An oxazole-based compound 98 was developed by Li and Woster [ 172 ] in an attempt to structurally mimic the benzamide ZBG and simultaneously reduce the potential metabolic toxicity.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Pharmacokinetic assessment showed a half-life time of 93 min in mouse liver microsomes, as well as potential for glucuronidation, but no general cytotoxicity against human dermal fibroblast cells [ 170 ]. Further studies by Haney et al [ 171 ] identified 97 , which showed antiproliferative activities in the range of 1–11 µM against three different myeloma cell lines and exhibited a different apoptosis mechanism as a function of gene expression patterns compared to SAHA. An oxazole-based compound 98 was developed by Li and Woster [ 172 ] in an attempt to structurally mimic the benzamide ZBG and simultaneously reduce the potential metabolic toxicity.…”
Section: Miscellaneousmentioning
confidence: 99%
“…[ 69 ] Inhibiting the expression of PI3K could enhance cell autophagy and apoptosis by regulating the PI3K/Akt/mTOR pathway. [ 70 , 71 ] MicroRNAs have been implicated in many critical cellular processes including apoptosis. Moreover, miR-630 maintains the apoptotic balance by targeting multiple modulators, such as poly (ADP-ribose) polymerase family member 3 (PARP3), DNA damage inducible transcript 4 (DDIT4), E1A binding protein p300 (EP300) and EP300 downstream effector p53.…”
Section: Discussionmentioning
confidence: 99%
“…MO-OH-Nap, but not SAHA, promotes the expression of markers associated with endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) in MM cells. MO-OH-Nap also displayed synergistic effects when used in conjunction with the proteasome inhibitor bortezomib but in a manner that was independent of aggresome formation [15]. These findings prompted further investigation into MO-OH-Nap's mechanism of action in MM.…”
Section: Introductionmentioning
confidence: 95%
“…Thus there continues to be a need for novel treatment strategies. Recently, our group examined the activity of six novel α-substituted tropolones, including MO-OH-Nap (2-hydroxy-7-naphthalene-2-ylcyclohepta-2,4,6-trienone), in MM cells and demonstrated that MO-OH-Nap induces caspase cleavage in a time frame distinct from that of the pan-HDAC inhibitor suberoylanilide hydroxamic acid (SAHA) [15]. MO-OH-Nap, but not SAHA, promotes the expression of markers associated with endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) in MM cells.…”
Section: Introductionmentioning
confidence: 99%